Mechanical and thermo-physical properties of polymesodabengalensis reinforced polymer-matrix composites / Mahshuri Yusof - Mahshuri , Yusof (2018)
The main objective of this research is to investigate the effect of including calcium carbonate (CaCO3) from lokan, a local clam shell, in varying micron sizes and particle contents to unsaturated polyester (UPE) on the mechanical and thermophysical properties of UPE/CaCO3 composites. The first part of this research involves characterizing the particle of lokan clam shell, which is scientifically known as Polymesoda bengalensis. The polymorph of the particle is identified by X-ray diffraction (XRD) and its morphology is observed by scanning electron microscope (SEM). The study reveals that the particle consists entirely of CaCO3 of aragonite polymorph. The SEM indicates that the aragonite is in the form of rod-like crystals. The filler used for this study, aragonite CaCO3, is ground and graded into eight different mean sizes, treated with 1 wt% stearic acid, then reinforced into UPE resin. The samples are fabricated through ultrasonication and open molding method at room temperature according to the different filler weight fractions (2, 4, 6 and 8 wt%) and sizes. Tensile, compressive and flexural tests are done according to ASTM D638, ASTM D695 and ASTM D790, respectively. Vickers hardness testing is conducted at 245.2 mN for a 20 seconds indentation period. The Tabor number, or correlation between hardness and ultimate compressive strength,